Ventricular arrhythmias and cardiac arrest in aconitine poisoning: a case report - Nino Cmor; Gašper Razinger; Jure Fluher; Andrej Markota (Acta Medico-Biotechnica, 2024)
In traditional Chinese medicine, aconitum plants and roots are frequently used after extensive processing to treat various ailments in humans. However, use of a larger than recommended dose and inadequate processing increase the risk of aconitine poisoning. As a result of its particular mechanism of toxicity, aconitine poisoning can present with a variety of arrhythmias, including ventricular ectopy, ventricular tachycardia, ventricular fibrillation, and torsades de pointes. Meticulous arrythmia treatment is needed to restore sinus rhythm. We report a case of ventricular arrhythmias (VAs) induced by accidental aconitine poisoning. Our case highlights the efficacy of amiodarone in treating aconitine-induced VAs. To the best of our knowledge, this is one of the first described cases of aconitine-induced VAs in Europe. Clinicians should be aware of potential rare toxicological causes of malignant arrhythmias and consider toxicological screening in otherwise etiologically unexplained sudden cardiac arrest.